Typical and atypical pathology in primary progressive aphasia variants - Spinelli, Edoardo G.; Mandelli, Maria Luisa; Miller, Zachary A.; Santos‐Santos, Miguel A; Wilson, Stephen M.; Agosta, Federica; Grinberg, Lea T.; Huang, Eric J.; Trojanowski, John Q.; Meyer, Marita; Henry, Maya L.; Comi, Giancarlo; et al. (Annals of neurology, 2017)
Objective To characterize in vivo signatures of pathological diagnosis in a large cohort of patients with primary progressive aphasia (PPA) variants defined by current diagnostic classification. Methods Extensive clinical, cognitive, neuroimaging, and neuropathological data were collected from 69 patients with sporadic PPA, divided into 29 semantic (svPPA), 25 nonfluent (nfvPPA), 11 logopenic (lvPPA), and 4 mixed PPA. Patterns of gray matter (GM) and white matter (WM) atrophy at presentation were assessed and tested as predictors of pathological diagnosis using support vector machine (SVM) algorithms. Results A clinical diagnosis of PPA was associated with frontotemporal lobar degeneration (FTLD) with transactive response DNA‐binding protein (TDP) inclusions in 40.5%, FTLD‐tau in 40.5%, and Alzheimer disease (AD) pathology in 19% of cases. Each variant was associated with 1 typical pathology; 24 of 29 (83%) svPPA showed FTLD‐TDP type C, 22 of 25 (88%) nfvPPA showed FTLD‐tau, and all 11 lvPPA had AD. Within FTLD‐tau, 4R‐tau pathology was commonly associated with nfvPPA, whereas Pick disease was observed in a minority of subjects across all variants except for lvPPA. Compared with pathologically typical cases, svPPA‐tau showed significant extrapyramidal signs, greater executive impairment, and severe striatal and frontal GM and WM atrophy. nfvPPA‐TDP patients lacked general motor symptoms or significant WM atrophy. Combining GM and WM volumes, SVM analysis showed 92.7% accuracy to distinguish FTLD‐tau and FTLD‐TDP pathologies across variants. Interpretation Each PPA clinical variant is associated with a typical and most frequent cognitive, neuroimaging, and neuropathological profile. Specific clinical and early anatomical features may suggest rare and atypical pathological diagnosis in vivo. Ann Neurol 2017;81:430–443